Monopoly Under General Equilibrium: Comment - Bishop, Robert L. (Quarterly Journal of Economics, 1966)
Introduction, 652. — I. Assumptions, 652. — II. The cost-minimizing locus, 653. — II. Relationships of the cost-minimizing and efficiency loci, 655. — IV. The interdependence of cost and demand, 656. — V. Conclusion, 658.